Man of Steel : the early years : junior novel - Whitman, Frank (New York: HarperFestival, 2013)
Follows Clark Kent's childhood before he became Superman.
5.3
3-6
Keywords: Superman (Fictitious character) -- Juvenile fiction; Superheroes -- Juvenile fiction; Superman (Fictitious character) -- Fiction; Superheroes -- Fiction; Movie novels